Saharan dust transport studied by airborne Doppler wind lidar and numerical models - Chouza Keil, Fernando (Ludwig-Maximilians-Universität München, 2016)
Every year a large amount of dust is transported over the north Atlantic ocean from North Africa into the Caribbean region. Despite the progress made during the last decades in the understanding and modeling of this process, many uncertainties still remain. In this cumulative thesis, the airborne Doppler wind lidar (DWL) measurements performed during the SALTRACE campaign (June-July 2013), large eddy simulations and the global atmospheric composition model MACC are used to study different aspects of the dust transport process and evaluate the current modeling capabilities. As part of this work, a novel calibration algorithm for the retrieval of quantitative aerosol backscatter and extinction coefficients from the DWL measurements is introduced. This calibration procedure relies on the simultaneous measurement of the same atmospheric volume by the airborne DWL and an aerosol ground-based lidar. This method is then validated with satellite lidar CALIOP and ground-based lidar measurements. Additionally, improvements in vertical wind retrieval algorithms are discussed and their impact on the retrieval accuracy estimated by means of two different methods. Based on this extended airborne DWL dataset, which includes simultaneous backscatter and wind measurements, different processes associated with the Saharan dust transport are investigated. Measurements carried out in the Cabo Verde and Barbados regions revealed the presence of island-induced gravity waves. These measurements are used in combination with in-situ wind and particle number density retrievals, large eddy simulations, and wavelet analysis to determine the main characteristics of the observed waves and their interaction with the Saharan Air Layer. Finally, DWL and CALIOP measurements are used to evaluate the capabilities of the MACC global aerosol model to reproduce the Saharan dust long-range transport process during SALTRACE. A comparison and analysis of the measured and simulated average wind and dust distributions in the West African and Caribbean regions is presented. Three case studies covering different characteristic features, like the African Easterly Jet and the dust transport modulation by the African Easterly Waves, are discussed with an outlook to future campaigns and the assimilation of the data products for the ESA's future satellite missions Aeolus and EarthCARE.